Prevalence and Severity of Gingivitis Among 19–22-Year-Old Patients Attending Private Dental College, Chennai: A Hospital Based Cross-Sectional Study - T, PRIADARSINI; PRABAKAR, JAYASHRI; GANAPTHY, DHANRAJ (The journal of contemporary issues in business and government, 2021)
Gingivitis is the most common form of periodontal disease which is considered to be the second most common oral disease affecting more than 75% of the population worldwide. The main objective of this study was to evaluate the prevalence and severity of gingivitis among 19- 22 years old South-Indian population visiting Saveetha dental college , Chennai. This study included the data of 165 patients who visited Saveetha Dental college in the period of June 2019 - March 2020. The required data was collected from the patient records and their Gingival index score was taken into account. Data was entered in Microsoft excel spreadsheet and analysed using IBM SPSS software version 20.O(Armonk, NY: IBM. Corp).Numerical data were presented as mean and standard deviation values. For the test, a p value of <0.05 is to be considered statistically significant.Shapiro Wilks test used to test the normality of the data set.Gingival index scores were continuous variables. Hence, it was presented as mean and standard deviation values. Independent T test was used to find the difference between the different age groups and gender with respect to the mean Gingival index score. Of the 165 people, 109 were male and 56 were female patients of the age group 19-22 years. Gingivitis is found to be more severe in 21-22 year old patients than patients who are 19-20 years old. Also, Gingivitis is highly prevalent in the male population with the mean gingival index score of 1.29 than females.